A lightweight power cable for ships and a processing method thereof
By using conductive cores, wrapping tapes, tinned copper wire braided layer and crosslinked polyolefin outer sheath in the cable, and using crosslinked polyethylene insulating layer materials and composite additives, the mechanical properties of the cable are solved. The problem of poor thermal stability and insulation performance has achieved efficient and economical lightweight cable preparation.
Patent Information
- Application Number
- CN202411452018.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-17
AI Technical Summary
The mechanical properties, thermal stability and insulation properties of existing cables are poor, making it difficult to meet the needs of lightweight power cables for ships.
The structural design of conductive core, wrapping tape, tin-plated copper wire braided layer and crosslinked polyolefin outer sheath is improved by the preparation of crosslinked polyethylene insulating layer materials and composite additives. Thermal stability.
It significantly improves the insulation performance, mechanical properties and thermal stability of the cable, and is suitable for lightweight power cables for ships, reducing the cable volume and outer diameter, improving the cargo capacity and storage space utilization, and reducing the preparation cost. .
Smart Images

Figure CN118956043B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of cable preparation, and in particular relates to a lightweight power cable for ships and a processing method thereof. Background Art
[0002] The shipping industry is gradually transitioning towards low-carbon, energy-saving, green and environmentally friendly aspects, which has put forward new requirements for shipbuilding. In the process of achieving energy conservation and emission reduction, the lightweighting of ships and their assembly settings is also a very important part. The lightweighting of loading equipment and the reduction of the outer diameter of cables can reduce the weight of the ship to reduce energy consumption, or improve the assembly capacity of cargo and fuel.
[0003] The Chinese utility model patent with announcement number CN 212303131 U discloses a lightweight overhead insulated cable, which belongs to the technical field of power cables, and includes an outer sheath, wherein the outer sheath is coated with steel wire armor, and the steel wire armor is coated with an isolation sleeve, and the isolation sleeve is coated with a wrapping tape, and the wrapping tape is coated with a support seat, and the outer wall of the support seat is provided with a conductor groove, and the interior of the support seat is provided with an annular hole, and the conductor groove is coated with an electrostatic shielding tape, and the electrostatic shielding tape is coated with an insulating shielding sleeve; an insulating net made of a lighter aluminum alloy is used, polytetrafluoroethylene is used and helium is filled in the polytetrafluoroethylene, so that the weight of the overall cable is lighter, so that the cable does not need to be buried underground, but can be well suspended, and it is more convenient and simple to transport, carry and lay, but the mechanical properties, thermal stability and insulation properties of the cable prepared by this method still have room for improvement. Summary of the invention
[0004] The object of the present invention is to provide a lightweight power cable for ships and a processing method thereof, so as to solve the technical problems of poor mechanical properties, thermal stability and insulation properties of the cable in the prior art.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] The present invention provides a lightweight power cable for ships, comprising a conductive core, a wrapping tape, a tinned copper wire braided layer and a cross-linked polyolefin outer sheath, wherein a plurality of conductive cores are Z-shaped or circular and are arranged in an annular array inside the cross-linked polyolefin outer sheath, the wrapping tape is arranged between the cross-linked polyolefin outer sheath and the conductive core, the tinned copper wire braided layer is arranged between the cross-linked polyolefin outer sheath and the wrapping tape, and the conductive core is composed of a conductive core and a cross-linked polyethylene insulation layer from the inside to the outside, wherein the cross-linked polyethylene insulation layer is prepared from diphenyl sulfone, 4,4'-difluorobenzophenone, 4,4'-dihydroxydiphenyl ether, resorcinol and polyethylene, and the cross-linked polyolefin outer sheath is prepared from polyethylene and a composite additive.
[0007] Preferably, the method for preparing the cross-linked polyethylene insulation layer material comprises the following steps:
[0008] Q1: Add diphenyl sulfone to a container filled with argon, heat to completely melt the diphenyl sulfone, then add 4,4'-difluorobenzophenone, 4,4'-dihydroxydiphenyl ether, resorcinol, sodium carbonate and potassium carbonate to the container, stir, heat and polymerize. After the polymerization is completed, add the polymer to deionized water, crush, wash and vacuum dry to obtain product 1;
[0009] Q2: Add product 1 and polyethylene to a torque rheometer, heat and stir, then add maleic anhydride to the torque rheometer, continue stirring to obtain a blend, then transfer the blend to a flat vulcanizer, hot press molding, and then hot press cross-linking. After the cross-linking is completed, cool rapidly to obtain a cross-linked polyethylene insulation layer material.
[0010] In the above process, the synthetic reaction formula of product 1 is as follows:
[0011]
[0012] Preferably, in Q1, the mass ratio of diphenyl sulfone, 4,4'-difluorobenzophenone, 4,4'-dihydroxydiphenyl ether, resorcinol, sodium carbonate and potassium carbonate is (133.5-267): (33.39-66.78): (9.1-18.2): (19.55-39.1): (19.08-38.16): (0.21-0.42), the heating temperature is 130-140°C, and the heating temperature is 150-180°C. The warm polymerization reaction process is as follows: first, the temperature is raised to 200°C, and after staying for 2 hours, the temperature is raised to 250°C, and after staying for 1 hour, the temperature is raised to 290°C, and after staying for 1 hour, the temperature is raised to 310°C, and the reaction is carried out for 5 hours. The usage ratio of polymer to deionized water is (200-300) g: (3-4.5) L. Ethanol and deionized water are used for washing 8-10 times respectively. The vacuum drying temperature is 120-140°C, and the time is 10-12 hours.
[0013] Preferably, in Q2, the amount ratio of product 1, polyethylene and maleic anhydride is (0.4-1.2) g: (50-80) g: (0.1-0.3) g, the heating and stirring temperature is 110-120°C, the stirring time is 3-5 min, the rotation speed is 60-80 rpm, the continued stirring time is 3-5 min, and the hot pressing molding process is: at 110°C, the pressure is increased from 5 MPa to 15 MPa as a gradient, and each pressure is maintained for 5 min. The hot pressing cross-linking temperature is 175-180°C, the pressure is 15 MPa, and the cross-linking time is 30-45 min.
[0014] Preferably, the preparation method of the composite auxiliary agent comprises the following steps:
[0015] S1: Add 3-bromobenzyl alcohol to a container containing dichloromethane, then add imidazole and tert-butyldimethylsilyl chloride, react in an ice bath, extract after the reaction, collect the organic phase, dry, and remove the solvent by rotary evaporation to obtain a colorless liquid to obtain compound 1;
[0016] S2: Under a nitrogen atmosphere, sodium tert-butoxide and xylene are added to a container, heated and stirred, and then a mixed solution of propylene dicyandiamide and xylene is added to the container, and then compound 1 and bistriphenylphosphine palladium dibromide are dissolved in xylene and then added dropwise to the container, heated and stirred, and then dilute hydrochloric acid is added to terminate the reaction, filtered, extracted, and the solvent is removed by rotary evaporation, and purified to obtain compound 2;
[0017] S3: Compound 2 is dissolved in dichloromethane, potassium hydroxide solution is added, potassium ferrocyanide is added after stirring to react, and after the reaction is completed, it is purified, and added to a mixture of dichloromethane and tetramethylammonium fluoride, mixed and stirred, and purified to obtain compound 3;
[0018] S4: After drying the polybutylene glycol, add it to dimethylformamide, then add isophorone diisocyanate and dibutyltin dilaurate, heat and react under a nitrogen atmosphere to obtain a prepolymer, then mix and stir the prepolymer, triethanolamine and compound 3, heat and react to obtain a composite auxiliary agent.
[0019] In the above process, in the presence of imidazole, tert-butyldimethylsilyl chloride reacts with the hydroxyl group in 3-bromobenzyl alcohol to generate a silyl ether to obtain compound 1; then compound 1 reacts with propylene dicyanide under the condition of bistriphenylphosphine palladium dibromide as a catalyst to generate a cyanation reaction to obtain compound 2; then compound 2 reacts with potassium ferrocyanide as an oxidant, and reacts with tetramethylammonium fluoride to obtain compound 3; polybutylene glycol reacts with isophorone diisocyanate to generate a prepolymer, and then the hydroxyl group in compound 3 reacts with the hydroxyl group in triethanolamine and the isocyanate group in the prepolymer to obtain a composite auxiliary agent, wherein the synthesis reaction formula of the composite auxiliary agent is as follows:
[0020]
[0021] The results of mass spectrometry analysis of compound 1 were: m / z: 302.05 (100.0%), 300.05 (99.4%), 301.06(14.3%), 303.06 (14.0%), 303.05 (5.4%), 301.05 (5.0%), 304.05 (3.2%), 302.06(1.9%), 304.06 (1.9%); the results of mass spectrometry analysis of compound 2 were: m / z: 570.28 (100.0%), 571.29(35.2%), 571.28 (11.6%), 572.29 (10.5%), 572.28 (7.1%), 573.28 (2.8%), 573.29 (1.6%); the results of mass spectrometry analysis of compound 3 were: m / z: 342.11 (100.0%), 343.12 (21.9%), 344.12 (2.7%), 343.11 (1.5%).
[0022] Preferably, in S1, the molar ratio of 3-bromobenzyl alcohol and tert-butyldimethylsilyl chloride is (1-2): (1.1-2.1), the ice bath reaction time is 10-12h, the extraction is carried out with distilled water and dichloromethane, and the mixture is dried with anhydrous sodium sulfate; in S2, the heating and stirring temperature is 50-60°C, the time is 30-45min, the molar ratio of compound 1 and malonic acid is (1-1.5): (1-1.6), the heating and stirring temperature is 110-120°C, the time is 8-10h, the volume fraction of dilute hydrochloric acid is 10vt%, ethyl acetate is added for filtration, saturated sodium chloride solution is used for extraction, a mixed solution of petroleum ether and dichloromethane with a volume ratio of 6:4 is used as the eluent, and the mixture is purified by column chromatography.
[0023] Preferably, in S3, the molar ratio of compound 2 to tetramethylammonium fluoride is (1-1.5):(2-3), the concentration of potassium hydroxide solution is 0.3 mol / L, the stirring time is 10-15 min, the reaction time is 10-20 min, and the mixing and stirring time is 10-12 h; in S4, the molar ratio of polybutylene glycol to isophorone diisocyanate is (1-2):(2-4), the drying temperature of polybutylene glycol is 90-100°C, the time is 3-5 h, the heating reaction temperature is 60-80°C, the time is 2-4 h, the molar ratio of prepolymer, triethylamine and compound 3 is (1-2):(1-2):(1.1-2.1), the heating reaction temperature is 75-85°C, and the time is 20-24 h.
[0024] Preferably, the processing method of the lightweight power cable for ships comprises the following steps:
[0025] Step 1: adding polyethylene and composite additives into a torque rheometer, adding maleic anhydride, heating for cross-linking, and granulating to obtain a cross-linked polyolefin outer sheath material;
[0026] Step 2: Twisting the conductive core by Z-shaped conductor drawing, and then wrapping the cross-linked polyethylene insulation layer on the surface of the conductive core, and pressing tightly to obtain the conductive core;
[0027] Step three: Then wrap the wrapping tape on the surface of the conductive core, and then wrap the tinned copper wire braid on the surface of the wrapping tape to obtain a tinned copper wire braided layer, and then wrap the tinned copper wire braided layer with a cross-linked polyolefin outer sheath material and press it tightly to obtain a lightweight power cable for ships.
[0028] Preferably, in step 1, the usage ratio of polyethylene, composite auxiliary agent and maleic anhydride is (70-80) g: (2-8) g: (1-2) g.
[0029] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0030] 1. The present invention first uses 4,4'-difluorobenzophenone, 4,4'-dihydroxydiphenyl ether, resorcinol and polyethylene as raw materials to prepare a cross-linked polyethylene insulation layer material, then uses 3-bromobenzyl alcohol, propylene dicyandiamide, potassium ferrocyanide, polybutylene glycol and isophorone diisocyanate as raw materials to prepare a composite auxiliary agent, which is added to polyethylene to obtain a cross-linked polyolefin outer sheath material, and the obtained substance is applied to a cable to effectively improve the insulation performance, mechanical properties and thermal stability of the cable. It is applied to ships to increase the cargo capacity, and the prepared cable has a smaller volume and a smaller cable outer diameter, so that the space in the cabin can be fully utilized, and the storage space is larger. At the same time, compared with the preparation of traditional cables, the cable prepared by this method has a lower cost and increased economy.
[0031] 2. The present invention uses 4,4'-difluorobenzophenone, 4,4'-dihydroxydiphenyl ether, resorcinol and polyethylene as raw materials to prepare a cross-linked polyethylene insulation layer material. The aromatic rings and polar groups contained in the product 1 work together to limit the flow of charges, effectively prevent the passage of current, and improve the insulation performance of the cable. The obtained product 1 can also maintain a low dielectric constant and dielectric loss at high frequencies, which means that in a high-frequency electric field, the insulation performance is stable and will not significantly decrease due to changes in the frequency of the electric field; the obtained product 1 has an excellent glass transition temperature, so that the cross-linked polyethylene insulation layer material can still maintain its performance at a higher temperature, and the contained benzene rings and rigid groups also make the product 1 have high temperature resistance. Applying it to cables can effectively improve the thermal stability of the cables; and the molecular chain structure in the product 1 is tight and regular, so that the obtained insulation layer material has extremely high strength and toughness, so that it can resist deformation and damage, and ensure the excellent mechanical properties of the cable.
[0032] 3. The present invention uses 3-bromobenzyl alcohol, propylene dicyandiamide, potassium ferrocyanide, polybutylene glycol and isophorone diisocyanate as raw materials to prepare a composite auxiliary agent, which is added to polyethylene to obtain a cross-linked polyolefin outer sheath material. The aromatic groups contained in the composite auxiliary agent can be connected with the polyurethane segments in the polyurethane network, thereby improving the overall rigidity and toughness of the material, so that when it is subjected to external force, the existence of interaction can effectively transfer and disperse stress, so that the cable exhibits higher strength and modulus, thereby enhancing mechanical properties; and the polyurethane segments in the prepolymer have excellent thermal stability, can maintain structural integrity under high temperature environment, so that the obtained cross-linked polyolefin outer sheath material also has excellent thermal stability; at the same time, the presence of the polyurethane structure helps to prevent the flow and leakage of charges, and improves the insulation performance of the cross-linked polyolefin outer sheath material. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0034] Figure 1 It is a cross-sectional schematic diagram of a lightweight power cable for ships prepared by the present invention;
[0035] Figure 2 This is a schematic diagram of the first conductive core structure of the lightweight power cable for ships prepared by the present invention;
[0036] Figure 3 This is a schematic diagram of the second conductive core structure of the lightweight power cable for ships prepared by the present invention;
[0037] Figure 4 This is a schematic diagram of the third conductive core structure of the lightweight power cable for ships prepared by the present invention;
[0038] Figure 5 It is a schematic diagram of the fourth conductive core structure of the lightweight power cable for ships prepared by the present invention.
[0039] Description of the drawings: 1-1. Conductive core, 1-2. Cross-linked polyethylene insulation layer, 1. Conductive core, 2. Wrapping tape, 3. Tinned copper wire braided layer, 4. Cross-linked polyolefin outer sheath. DETAILED DESCRIPTION
[0040] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Embodiment 1
[0041] See also Figure 1-5 As shown, the ship lightweight power cable comprises a conductive core 1, a wrapping tape 2, a tinned copper wire braided layer 3 and a cross-linked polyolefin outer sheath 4, a plurality of conductive cores 1 are arranged in a Z-shaped array inside the cross-linked polyolefin outer sheath 4, the wrapping tape 2 is arranged between the cross-linked polyolefin outer sheath 4 and the conductive core 1, the tinned copper wire braided layer 3 is arranged between the cross-linked polyolefin outer sheath 4 and the wrapping tape 2, and the conductive core 1 is composed of a conductive core 1-1 and a cross-linked polyethylene insulation layer 1-2 from the inside to the outside. The conductive core 1-1 is bare copper or tinned copper. Embodiment 2
[0042] This embodiment discloses a method for preparing a cross-linked polyethylene insulation layer material, comprising the following steps:
[0043] Q1: 200.3 g of diphenyl sulfone was added to a container filled with argon, and the mixture was heated to 130°C to completely melt the diphenyl sulfone. Then, 50.09 g of 4,4'-difluorobenzophenone, 13.65 g of 4,4'-dihydroxydiphenyl ether, 39.33 g of resorcinol, 28.62 g of sodium carbonate and 0.32 g of potassium carbonate were added to the container, and the mixture was stirred and heated for polymerization. The polymerization process was as follows: first, the temperature was raised to 200°C, and the mixture was kept for 2 hours. Then, the temperature was raised to 250°C, and the mixture was kept for 1 hour. Then, the temperature was raised to 290°C, and the mixture was kept for 1 hour. Then, the temperature was raised to 310°C, and the reaction was carried out for 5 hours. After the polymerization was completed, 250 g of the polymer was added to 3.75 L of deionized water, crushed, washed 10 times with ethanol and deionized water respectively, and dried under vacuum at 140°C for 10 hours to obtain product 1.
[0044] Q2: 0.8 g of product 1 and 65 g of polyethylene were added to a torque rheometer, stirred at 60 rpm and 110°C for 5 min, and then 0.2 g of maleic anhydride was added to the torque rheometer, and stirring was continued for 5 min to obtain a blend. The blend was then transferred to a flat vulcanizer and hot-pressed. The process was as follows: the pressure was increased from 5 MPa to 15 MPa at 110°C, and each pressure was maintained for 5 min. Then, hot-press crosslinking was performed at 180°C and 15 MPa for 45 min. After the crosslinking was completed, it was rapidly cooled to obtain a cross-linked polyethylene insulation layer material.
[0045] This embodiment discloses a method for preparing a composite auxiliary agent, comprising the following steps:
[0046] S1: 0.96 mL of 3-bromobenzyl alcohol was added to a container containing 5 mL of dichloromethane, and then 0.43 g of imidazole and 1.29 g of tert-butyldimethylsilyl chloride were added. The reaction was carried out in an ice bath for 12 h. After the reaction was completed, the mixture was extracted with distilled water and dichloromethane. The organic phase was collected and dried with anhydrous sodium sulfate. The solvent was removed by rotary evaporation to obtain a colorless liquid to obtain compound 1;
[0047] S2: Under a nitrogen atmosphere, 0.4 g of sodium tert-butoxide and 20 mL of xylene were added to a container. After heating and stirring at 60°C for 45 min, a mixed solution of 0.81 g of propylene glycol and 10 mL of xylene was added to the container. Then, 3.99 g of compound 1 and 0.04 g of bistriphenylphosphine palladium dibromide were dissolved in 15 mL of xylene and then added dropwise to the container. The mixture was stirred at 120°C for 10 h. Subsequently, 10% by volume of dilute hydrochloric acid was added to terminate the reaction. Ethyl acetate was added for filtration. Saturated sodium chloride solution was used for extraction. The solvent was removed by rotary evaporation. A mixed solution of petroleum ether and dichloromethane in a volume ratio of 6:4 was used as the eluent. The mixture was purified by column chromatography to obtain compound 2.
[0048] S3: 1.64 g of compound 2 was dissolved in 15 mL of dichloromethane, 15 mL of 0.3 mol / L potassium hydroxide solution was added, and 0.07 g of potassium ferrocyanide was added after stirring for 15 min and reacted for 20 min. After the reaction was completed, the mixture was purified and added to a mixture of 15 mL of dichloromethane and 0.84 g of tetramethylammonium fluoride, mixed and stirred for 12 h, and purified to obtain compound 3;
[0049] S4: 6.75 g of polybutylene glycol with a relative molecular mass of 1000 was dried at 90°C for 5 h and then added to 20 mL of dimethylformamide, followed by the addition of 3 g of isophorone diisocyanate and 0.4 g of dibutyltin dilaurate, and reacted at 60°C for 4 h under a nitrogen atmosphere to obtain a prepolymer, and then 15 g of the prepolymer, 1.26 g of triethanolamine and 4.57 g of compound 3 were mixed and stirred, and heated at 80°C for 24 h to obtain a composite auxiliary agent.
[0050] This embodiment discloses a method for processing a lightweight power cable for ships, comprising the following steps:
[0051] Step 1: Add 75g of polyethylene and 5g of composite additive into a torque rheometer, add 1.5g of maleic anhydride, heat for crosslinking, and granulate to obtain a crosslinked polyolefin outer sheath material;
[0052] Step 2: Twisting the conductive core by Z-shaped conductor drawing, and then wrapping the cross-linked polyethylene insulation layer on the surface of the conductive core, and pressing tightly to obtain the conductive core;
[0053] Step three: Then wrap the wrapping tape on the surface of the conductive core, and then wrap the tinned copper wire braid on the surface of the wrapping tape to obtain a tinned copper wire braided layer, and then wrap the tinned copper wire braided layer with a cross-linked polyolefin outer sheath material and press it tightly to obtain a lightweight power cable for ships. Embodiment 3
[0054] This embodiment discloses a method for preparing a cross-linked polyethylene insulation layer material, comprising the following steps:
[0055] Q1: 133.5 g of diphenyl sulfone was added to a container filled with argon, and the mixture was heated to 130°C to completely melt the diphenyl sulfone. Then, 33.69 g of 4,4'-difluorobenzophenone, 9.1 g of 4,4'-dihydroxydiphenyl ether, 19.55 g of resorcinol, 19.08 g of sodium carbonate and 0.21 g of potassium carbonate were added to the container, and the mixture was stirred and heated for polymerization. The polymerization reaction process was as follows: first, the temperature was raised to 200°C, and the mixture was kept for 2 hours. Then, the temperature was raised to 250°C, and the mixture was kept for 1 hour. Then, the temperature was raised to 290°C, and the mixture was kept for 1 hour. Then, the temperature was raised to 310°C, and the reaction was carried out for 5 hours. After the polymerization was completed, 200 g of the polymer was added to 3 L of deionized water, crushed, washed 10 times with ethanol and deionized water respectively, and dried under vacuum at 140°C for 10 hours to obtain product 1.
[0056] Q2: 0.4 g of product 1 and 50 g of polyethylene were added to a torque rheometer, stirred at 60 rpm and 110°C for 5 min, and then 0.1 g of maleic anhydride was added to the torque rheometer, and stirring was continued for 5 min to obtain a blend. The blend was then transferred to a flat vulcanizer and hot-pressed. The process was: the pressure was increased from 5 MPa to 15 MPa at 110°C, and each pressure was maintained for 5 min. Then, hot-press cross-linking was performed at 180°C and 15 MPa for 45 min. After the cross-linking was completed, it was rapidly cooled to obtain a cross-linked polyethylene insulation layer material.
[0057] This embodiment discloses a method for preparing a composite auxiliary agent, comprising the following steps:
[0058] S1: 0.64 mL of 3-bromobenzyl alcohol was added to a container containing 5 mL of dichloromethane, and then 0.43 g of imidazole and 0.89 g of tert-butyldimethylsilyl chloride were added. The reaction was carried out in an ice bath for 12 h. After the reaction was completed, the mixture was extracted with distilled water and dichloromethane. The organic phase was collected and dried with anhydrous sodium sulfate. The solvent was removed by rotary evaporation to obtain a colorless liquid to obtain compound 1;
[0059] S2: Under a nitrogen atmosphere, 0.4 g of sodium tert-butoxide and 20 mL of xylene were added to a container. After heating and stirring at 60°C for 45 min, a mixed solution of 0.63 g of propylene glycol and 10 mL of xylene was added to the container. Then, 3.18 g of compound 1 and 0.04 g of bistriphenylphosphine palladium dibromide were dissolved in 15 mL of xylene and then added dropwise to the container. The mixture was stirred at 120°C for 10 h. Subsequently, 10% by volume of dilute hydrochloric acid was added to terminate the reaction. Ethyl acetate was added for filtration. Saturated sodium chloride solution was used for extraction. The solvent was removed by rotary evaporation. A mixed solution of petroleum ether and dichloromethane in a volume ratio of 6:4 was used as the eluent. The mixture was purified by column chromatography to obtain compound 2.
[0060] S3: 1.31 g of compound 2 was dissolved in 15 mL of dichloromethane, 15 mL of 0.3 mol / L potassium hydroxide solution was added, and 0.07 g of potassium ferrocyanide was added after stirring for 15 min and reacted for 20 min. After the reaction was completed, the mixture was purified and added to a mixture of 15 mL of dichloromethane and 0.67 g of tetramethylammonium fluoride, mixed and stirred for 12 h, and purified to obtain compound 3;
[0061] S4: 4.5 g of polybutylene glycol with a relative molecular mass of 1000 was dried at 90°C for 5 h and then added to 20 mL of dimethylformamide, followed by the addition of 2 g of isophorone diisocyanate and 0.4 g of dibutyltin dilaurate, and reacted at 60°C for 4 h under a nitrogen atmosphere to obtain a prepolymer, and then 10 g of the prepolymer, 0.84 g of triethanolamine and 3.14 g of compound 3 were mixed and stirred, and heated at 80°C for 24 h to obtain a composite auxiliary agent.
[0062] This embodiment discloses a method for processing a lightweight power cable for ships, comprising the following steps:
[0063] Step 1: Add 70g polyethylene and 2g composite additive into a torque rheometer, add 1g maleic anhydride, heat for crosslinking, and granulate to obtain a crosslinked polyolefin outer sheath material;
[0064] Step 2: Twisting the conductive core by Z-shaped conductor drawing, and then wrapping the cross-linked polyethylene insulation layer on the surface of the conductive core, and pressing tightly to obtain the conductive core;
[0065] Step three: Then wrap the wrapping tape on the surface of the conductive core, and then wrap the tinned copper wire braid on the surface of the wrapping tape to obtain a tinned copper wire braided layer, and then wrap the tinned copper wire braided layer with a cross-linked polyolefin outer sheath material and press it tightly to obtain a lightweight power cable for ships. Embodiment 4
[0066] This embodiment discloses a method for preparing a cross-linked polyethylene insulation layer material, comprising the following steps:
[0067] Q1: 267g of diphenyl sulfone was added to a container filled with argon, and the mixture was heated to 130°C to completely melt the diphenyl sulfone. Then, 66.78g of 4,4'-difluorobenzophenone, 18.2g of 4,4'-dihydroxydiphenyl ether, 39.1g of resorcinol, 38.16g of sodium carbonate and 0.42g of potassium carbonate were added to the container, and the mixture was stirred and heated for polymerization. The polymerization reaction process was as follows: first, the temperature was raised to 200°C, and the mixture was kept for 2h. Then, the temperature was raised to 250°C, and the mixture was kept for 1h. Then, the temperature was raised to 290°C, and the mixture was kept for 1h. Then, the temperature was raised to 310°C, and the reaction was carried out for 5h. After the polymerization was completed, 300g of the polymer was added to 4.5L of deionized water, crushed, washed 10 times with ethanol and deionized water respectively, and dried under vacuum at 140°C for 10h to obtain product 1.
[0068] Q2: 1.2 g of product 1 and 80 g of polyethylene were added to a torque rheometer, stirred at 60 rpm and 110°C for 5 min, and then 0.3 g of maleic anhydride was added to the torque rheometer, and stirring was continued for 5 min to obtain a blend. The blend was then transferred to a flat vulcanizer and hot-pressed. The process was as follows: the pressure was increased from 5 MPa to 15 MPa at 110°C, and each pressure was maintained for 5 min. Then, hot-press cross-linking was performed at 180°C and 15 MPa for 45 min. After the cross-linking was completed, it was rapidly cooled to obtain a cross-linked polyethylene insulation layer material.
[0069] This embodiment discloses a method for preparing a composite auxiliary agent, comprising the following steps:
[0070] S1: 1.28 mL of 3-bromobenzyl alcohol was added to a container containing 5 mL of dichloromethane, and then 0.43 g of imidazole and 1.69 g of tert-butyldimethylsilyl chloride were added. The reaction was carried out in an ice bath for 12 h. After the reaction was completed, the mixture was extracted with distilled water and dichloromethane. The organic phase was collected and dried with anhydrous sodium sulfate. The solvent was removed by rotary evaporation to obtain a colorless liquid to obtain compound 1;
[0071] S2: Under a nitrogen atmosphere, 0.4 g of sodium tert-butoxide and 20 mL of xylene were added to a container. After heating and stirring at 60°C for 45 min, a mixed solution of 1 g of propylene glycol and 10 mL of xylene was added to the container. Then, 4.80 g of compound 1 and 0.04 g of bistriphenylphosphine palladium dibromide were dissolved in 15 mL of xylene and then added dropwise to the container. The mixture was stirred at 120°C for 10 h. Subsequently, 10% by volume of dilute hydrochloric acid was added to terminate the reaction. Ethyl acetate was added for filtration. Saturated sodium chloride solution was used for extraction. The solvent was removed by rotary evaporation. A mixed solution of petroleum ether and dichloromethane in a volume ratio of 6:4 was used as the eluent. The mixture was purified by column chromatography to obtain compound 2.
[0072] S3: 1.97 g of compound 2 was dissolved in 15 mL of dichloromethane, 15 mL of 0.3 mol / L potassium hydroxide solution was added, and 0.07 g of potassium ferrocyanide was added after stirring for 15 min and reacted for 20 min. After the reaction was completed, the mixture was purified and added to a mixture of 15 mL of dichloromethane and 1 g of tetramethylammonium fluoride, mixed and stirred for 12 h, and purified to obtain compound 3;
[0073] S4: 9 g of polybutylene glycol with a relative molecular mass of 1000 was dried at 90°C for 5 h and then added to 20 mL of dimethylformamide, followed by the addition of 4 g of isophorone diisocyanate and 0.4 g of dibutyltin dilaurate, and reacted at 60°C for 4 h under a nitrogen atmosphere to obtain a prepolymer, and then 20 g of the prepolymer, 1.68 g of triethanolamine and 5.99 g of compound 3 were mixed and stirred, and heated at 80°C for 24 h to obtain a composite auxiliary agent.
[0074] This embodiment discloses a method for processing a lightweight power cable for ships, comprising the following steps:
[0075] Step 1: Add 80g of polyethylene and 8g of composite additive into a torque rheometer, add 2g of maleic anhydride, heat for crosslinking, and granulate to obtain a crosslinked polyolefin outer sheath material;
[0076] Step 2: Twisting the conductive core by Z-shaped conductor drawing, and then wrapping the cross-linked polyethylene insulation layer on the surface of the conductive core, and pressing tightly to obtain the conductive core;
[0077] Step three: Then wrap the wrapping tape on the surface of the conductive core, and then wrap the tinned copper wire braid on the surface of the wrapping tape to obtain a tinned copper wire braided layer, and then wrap the tinned copper wire braided layer with a cross-linked polyolefin outer sheath material and press it tightly to obtain a lightweight power cable for ships. Embodiment 5
[0078] This embodiment discloses a method for preparing a cross-linked polyethylene insulation layer material, comprising the following steps:
[0079] Q1: 166.9 g of diphenyl sulfone was added to a container filled with argon, and the mixture was heated to 130°C to completely melt the diphenyl sulfone. Then, 41.89 g of 4,4'-difluorobenzophenone, 11.38 g of 4,4'-dihydroxydiphenyl ether, 29.44 g of resorcinol, 23.85 g of sodium carbonate and 0.27 g of potassium carbonate were added to the container, and the mixture was stirred and heated for polymerization. The polymerization process was as follows: first, the temperature was raised to 200°C, and the mixture was kept for 2 hours. Then, the temperature was raised to 250°C, and the mixture was kept for 1 hour. Then, the temperature was raised to 290°C, and the mixture was kept for 1 hour. Then, the temperature was raised to 310°C, and the reaction was carried out for 5 hours. After the polymerization was completed, 220 g of the polymer was added to 3.25 L of deionized water, crushed, washed 10 times with ethanol and deionized water respectively, and dried under vacuum at 140°C for 10 hours to obtain product 1.
[0080] Q2: 0.6 g of product 1 and 55 g of polyethylene were added to a torque rheometer, stirred at 60 rpm and 110°C for 5 min, and then 0.15 g of maleic anhydride was added to the torque rheometer, and stirring was continued for 5 min to obtain a blend. The blend was then transferred to a flat vulcanizer and hot-pressed. The process was as follows: the pressure was increased from 5 MPa to 15 MPa at 110°C, and each pressure was maintained for 5 min. Then, hot-press cross-linking was performed at 180°C and 15 MPa for 45 min. After the cross-linking was completed, it was rapidly cooled to obtain a cross-linked polyethylene insulation layer material.
[0081] This embodiment discloses a method for preparing a composite auxiliary agent, comprising the following steps:
[0082] S1: Add 0.77 mL of 3-bromobenzyl alcohol to a container containing 5 mL of dichloromethane, then add 0.43 g of imidazole and 1.09 g of tert-butyldimethylsilyl chloride, and react in an ice bath for 12 h. After the reaction is completed, extract with distilled water and dichloromethane, collect the organic phase, dry with anhydrous sodium sulfate, and remove the solvent by rotary evaporation to obtain a colorless liquid to obtain compound 1;
[0083] S2: Under a nitrogen atmosphere, 0.4 g of sodium tert-butoxide and 20 mL of xylene were added to a container. After heating and stirring at 60°C for 45 min, a mixed solution of 0.91 g of propylene glycol and 10 mL of xylene was added to the container. Then, 3.59 g of compound 1 and 0.04 g of bistriphenylphosphine palladium dibromide were dissolved in 15 mL of xylene and then added dropwise to the container. The mixture was stirred at 120°C for 10 h. Subsequently, 10% by volume of dilute hydrochloric acid was added to terminate the reaction. Ethyl acetate was added for filtration. Saturated sodium chloride solution was used for extraction. The solvent was removed by rotary evaporation. A mixed solution of petroleum ether and dichloromethane in a volume ratio of 6:4 was used as the eluent. The mixture was purified by column chromatography to obtain compound 2.
[0084] S3: 1.48 g of compound 2 was dissolved in 15 mL of dichloromethane, 15 mL of 0.3 mol / L potassium hydroxide solution was added, and 0.07 g of potassium ferrocyanide was added after stirring for 15 min and reacted for 20 min. After the reaction was completed, the mixture was purified and added to a mixture of 15 mL of dichloromethane and 0.92 g of tetramethylammonium fluoride, mixed and stirred for 12 h, and purified to obtain compound 3;
[0085] S4: 5.63 g of polybutylene glycol with a relative molecular mass of 1000 was dried at 90°C for 5 h and then added to 20 mL of dimethylformamide, followed by the addition of 2.5 g of isophorone diisocyanate and 0.4 g of dibutyltin dilaurate, and reacted at 60°C for 4 h under a nitrogen atmosphere to obtain a prepolymer, and then 12 g of the prepolymer, 1.05 g of triethanolamine and 3.86 g of compound 3 were mixed and stirred, and heated at 80°C for 24 h to obtain a composite auxiliary agent.
[0086] This embodiment discloses a method for processing a lightweight power cable for ships, comprising the following steps:
[0087] Step 1: Add 72g of polyethylene and 3g of composite additive into a torque rheometer, add 1.2g of maleic anhydride, heat for crosslinking, and granulate to obtain a crosslinked polyolefin outer sheath material;
[0088] Step 2: Twisting the conductive core by Z-shaped conductor drawing, and then wrapping the cross-linked polyethylene insulation layer on the surface of the conductive core, and pressing tightly to obtain the conductive core;
[0089] Step three: Then wrap the wrapping tape on the surface of the conductive core, and then wrap the tinned copper wire braid on the surface of the wrapping tape to obtain a tinned copper wire braided layer, and then wrap the tinned copper wire braided layer with a cross-linked polyolefin outer sheath material and press it tightly to obtain a lightweight power cable for ships.
[0090] Comparative Example 1
[0091] Comparative Example 1 Compared with Example 2, in the process of preparing the cross-linked polyethylene insulation layer material in Comparative Example 1, 4,4'-dihydroxydiphenyl ether was not added, and other conditions remained unchanged.
[0092] Comparative Example 2
[0093] Comparative Example 2 Compared with Example 2, in the process of preparing the composite auxiliary agent in Comparative Example 2, no malondicyandiamide was added, and other conditions remained unchanged.
[0094] Comparative Example 3
[0095] Comparative Example 3 Compared with Example 2, in the process of preparing the lightweight power cable for ships in Comparative Example 3, Product 1 is not added, and other conditions remain unchanged.
[0096] Comparative Example 4
[0097] Comparative Example 4 Compared with Example 2, in the process of preparing the lightweight power cable for ships in Comparative Example 4, no composite additive is added, and other conditions remain unchanged.
[0098] The performance of the lightweight power cables for ships prepared in Examples 2 to 5 and Comparative Examples 1 to 4 was tested. The thermal stability of the samples was tested according to GB / T 2951.32-2008. The mechanical properties of the samples were tested according to GB / T 2951.11-2008. The insulation properties of the insulating layer materials of the samples were tested using a volume resistivity meter. The test results are shown in Table 1:
[0099]
[0100] It can be seen from the test results in Table 1 that the lightweight power cables for ships prepared in Examples 2 to 5 of the present invention have excellent thermal stability, mechanical properties and insulation properties. By comparing Comparative Example 1 with Examples 2 to 5, it can be seen that the addition of 4,4'-dihydroxydiphenyl ether can effectively improve the thermal stability, mechanical properties and insulation properties of lightweight power cables for ships; by comparing Comparative Example 2 with Examples 2 to 5, it can be seen that the addition of propylene dicyandiamide can effectively improve the thermal stability, mechanical properties and insulation properties of lightweight power cables for ships; by comparing Comparative Example 3 with Examples 2 to 5, it can be seen that the addition of product 1 can effectively improve the thermal stability, mechanical properties and insulation properties of lightweight power cables for ships; by comparing Comparative Example 4 with Examples 2 to 5, it can be seen that the addition of composite additives can effectively improve the thermal stability, mechanical properties and insulation properties of lightweight power cables for ships.
[0101] The outer diameters of the conductive core prepared in Example 2 and the conventional tin-plated conductive core were measured and compared, and the test results are shown in Table 2:
[0102]
[0103] It can be seen from the test results in Table 2 that the conductive core prepared in Example 2 of the present invention has a smaller outer diameter than the conventional tin-plated conductive core, and therefore has a smaller volume, which is conducive to full utilization of the cabin space.
[0104] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A lightweight power cable for ships, characterized in that: It comprises a conductive core, a wrapping tape, a tinned copper wire braided layer and a cross-linked polyolefin outer sheath, wherein a plurality of conductive cores are Z-shaped or circular and are arranged in an annular array inside the cross-linked polyolefin outer sheath, the wrapping tape is arranged between the cross-linked polyolefin outer sheath and the conductive core, the tinned copper wire braided layer is arranged between the cross-linked polyolefin outer sheath and the wrapping tape, and the conductive core is composed of a conductive core and a cross-linked polyethylene insulation layer from the inside to the outside, wherein the cross-linked polyethylene insulation layer is prepared from diphenyl sulfone, 4,4'-difluorobenzophenone, 4,4'-dihydroxydiphenyl ether, resorcinol and polyethylene, and the cross-linked polyolefin outer sheath is prepared from polyethylene and a composite auxiliary agent; The preparation method of the cross-linked polyethylene insulation layer material comprises the following steps: Q1: Add diphenyl sulfone to a container filled with argon, heat to completely melt the diphenyl sulfone, then add 4,4'-difluorobenzophenone, 4,4'-dihydroxydiphenyl ether, resorcinol, sodium carbonate and potassium carbonate to the container, stir, heat and polymerize. After the polymerization is completed, add the polymer to deionized water, crush, wash and vacuum dry to obtain product 1; Q2: Add product 1 and polyethylene to a torque rheometer, heat and stir, then add maleic anhydride to the torque rheometer, continue stirring to obtain a blend, then transfer the blend to a flat vulcanizer, hot press molding, and then hot press cross-linking, after the cross-linking is completed, quickly cool to obtain a cross-linked polyethylene insulation layer material; The preparation method of the composite auxiliary agent comprises the following steps: S1: Add 3-bromobenzyl alcohol to a container containing dichloromethane, then add imidazole and tert-butyldimethylsilyl chloride, react in an ice bath, extract after the reaction, collect the organic phase, dry, and remove the solvent by rotary evaporation to obtain a colorless liquid to obtain compound 1; S2: Under a nitrogen atmosphere, sodium tert-butoxide and xylene are added to a container, heated and stirred, and then a mixed solution of propylene dicyandiamide and xylene is added to the container, and then compound 1 and bistriphenylphosphine palladium dibromide are dissolved in xylene and then added dropwise to the container, heated and stirred, and then dilute hydrochloric acid is added to terminate the reaction, filtered, extracted, and the solvent is removed by rotary evaporation, and purified to obtain compound 2; S3: Compound 2 is dissolved in dichloromethane, potassium hydroxide solution is added, potassium ferrocyanide is added after stirring to react, and after the reaction is completed, it is purified, and added to a mixture of dichloromethane and tetramethylammonium fluoride, mixed and stirred, and purified to obtain compound 3; S4: drying polybutylene glycol and adding it to dimethylformamide, then adding isophorone diisocyanate and dibutyltin dilaurate, heating and reacting under a nitrogen atmosphere to obtain a prepolymer, then mixing and stirring the prepolymer, triethanolamine and compound 3, and heating and reacting to obtain a composite auxiliary agent; The preparation method of the cross-linked polyolefin outer sheath material comprises: adding polyethylene and a composite auxiliary agent into a torque rheometer, adding maleic anhydride, heating for cross-linking, and granulating to obtain the cross-linked polyolefin outer sheath material; The polyethylene, composite auxiliary agent and maleic anhydride are used in a ratio of (70-80) g: (2-8) g: (1-2) g; In the Q1, the mass ratios of diphenyl sulfone, 4,4'-difluorobenzophenone, 4,4'-dihydroxydiphenyl ether, resorcinol, sodium carbonate and potassium carbonate are (133.5-267): (33.39-66.78): (9.1-18.2): (19.55-39.1): (19.08-38.16): (0.21-0.42), the heating temperature is 130-140°C, and the polymerization is carried out by heating. The reaction process is as follows: first, the temperature is raised to 200°C, and after staying for 2 hours, the temperature is raised to 250°C, and after staying for 1 hour, the temperature is raised to 290°C, and after staying for 1 hour, the temperature is raised to 310°C, and the reaction is carried out for 5 hours. The ratio of polymer to deionized water is (200-300) g: (3-4.5) L, and ethanol and deionized water are used for washing 8-10 times respectively. The vacuum drying temperature is 120-140°C, and the time is 10-12 hours. In Q2, the amount ratio of product 1, polyethylene and maleic anhydride is (0.4-1.2) g: (50-80) g: (0.1-0.3) g, the heating and stirring temperature is 110-120°C, the stirring time is 3-5 min, the rotation speed is 60-80 rpm, and the stirring time is continued for 3-5 min. The hot pressing molding process is: the pressure is increased from 5 MPa to 15 MPa at 110°C, and each pressure is maintained for 5 min. The hot pressing cross-linking temperature is 175-180°C, the pressure is 15 MPa, and the cross-linking time is 30-45 min. In S1, the molar ratio of 3-bromobenzyl alcohol and tert-butyldimethylsilyl chloride is (1-2): (1.1-2.1), the ice bath reaction time is 10-12 hours, the product is extracted with distilled water and dichloromethane, and dried with anhydrous sodium sulfate; in S2, the heating and stirring temperature is 50-60°C, the time is 30-45 minutes, the molar ratio of compound 1 and malonic acid is (1-1.5): (1-1.6), the heating and stirring temperature is 110-120°C, the time is 8-10 hours, the volume fraction of dilute hydrochloric acid is 10vt%, ethyl acetate is added for filtration, saturated sodium chloride solution is used for extraction, a mixed solution of petroleum ether and dichloromethane with a volume ratio of 6:4 is used as an eluent, and the product is purified by column chromatography; In S3, the molar ratio of compound 2 and tetramethylammonium fluoride is (1-1.5): (2-3), the concentration of potassium hydroxide solution is 0.3 mol / L, the stirring time is 10-15 min, the reaction time is 10-20 min, and the mixing and stirring time is 10-12 h. In S4, the molar ratio of polybutylene glycol and isophorone diisocyanate is (1-2): (2-4), the drying temperature of polybutylene glycol is 90-100°C, the reaction time is 3-5 h, the heating reaction temperature is 60-80°C, the time is 2-4 h, and the molar ratio of prepolymer, triethylamine and compound 3 is (1-2): (1-2): (1.1-2.1), the heating reaction temperature is 75-85°C, and the time is 20-24 h.
2. A method for processing a lightweight power cable for ships, characterized in that: The following steps are involved: Step 1: adding polyethylene and composite additives into a torque rheometer, adding maleic anhydride, heating for cross-linking, and granulating to obtain a cross-linked polyolefin outer sheath material; Step 2: Twisting the conductive core by Z-shaped conductor drawing, and then wrapping the cross-linked polyethylene insulation layer on the surface of the conductive core, and pressing tightly to obtain the conductive core; Step three: Then wrap the wrapping tape on the surface of the conductive core, and then wrap the tinned copper wire braid on the surface of the wrapping tape to obtain a tinned copper wire braided layer, and then wrap the tinned copper wire braided layer with a cross-linked polyolefin outer sheath material and press it tightly to obtain a lightweight power cable for ships.
Citation Information
Patent Citations
Lightweight overhead insulated cable
CN212303131U
Low-smoke power cable for ship
CN104008807A
Preparation method for high-flowability polyaryletherketone terpolymer containing side groups
CN110437437A